Effects of dietary minerals deficiency and supplementation on different parts of muscle minerals content in grazing Mongolian sheep - Meng, Lingbo; Jin, Xiwei; Qi, Zhi; Mi, Lan (Frontiers in Veterinary Science, 2024)
The objective of this study was to investigate the impact of dietary deficiency and supplementation of calcium, zinc, copper, cobalt, manganese or selenium on minerals content in the longissimus dorsi (LD), biceps femoris (BF) and triceps brachii (TB) of grazing Mongolian sheep.We randomly divided 98 sheep into 7 treatment groups and fed them specific diets for 60 days: a total mineral nutrition diet (LCG), a calcium deficiency diet (LCa), a zinc deficiency diet (LZn), a copper deficiency diet (LCu), a cobalt deficiency diet (LCo), a manganese deficiency diet (LMn) and a selenium deficiency diet (LSe). Then 7 sheep from each group were slaughtered and samples of LD, BF and TB were collected for mineral content analysis. The remaining sheep in each group were subsequently fed specific diets for an additional 41 days: a total mineral nutrition diet (SCG), a calcium supplementation diet (SCa), a zinc supplementation diet (SZn), a copper supplementation diet (SCu), a cobalt supplementation diet (SCo), a manganese supplementation diet (SMn) and a selenium supplementation diet (SSe). Afterward, all sheep were slaughtered, and muscle samples were collected and analyzed. Significant findings emerged that LCa decreased sulfur (S) content in BF and increased Ca content in LD and BF, while SCa increased S and Ca content in BF and TB, respectively (P<0.05). LZn decreased Zn, S, and potassium (K) content in LD and BF, while SZn